Identification of the novel HLA‐B*40:01:41 allele by polymerase chain reaction sequence‐based typing in a Chinese cord blood donor. (30th March 2017) - Chen, N.‐Y.; Wang, W.; Dong, L.‐N.; He, J.; Zhu, F.‐M.
Abstract : HLA‐B*40:01:41 differs from HLA‐B*40:01:01 by a single nucleotide substitution at position 195 G>A.